PEMANFAATAN MODEL PEMBELAJARAN FLIPPED CLASSROOM PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH DASAR ISLAM TERPADU - Destriani Destriani; Idi Warsah (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Kediri, 2022)
This paper aims to reveal the benefits of flipped classroom learning based on its application in the learning process in elementary schools. This study uses a qualitative research method with a descriptive type of research. The data sources were class observations and interviews with Islamic Religious Education (PAI) teachers and students at the Khoiru Ummah Integrated Islamic Elementary School (SDIT, Sekolah Dasar Islam Terpadu). The study results found that applying the flipped classroom learning model at SDIT Khoiru Ummah has two stages; pre-class and in-class. At the pre-class stage, the PAI teacher distributes learning videos for students to study before learning in class. While at the stage in the classroom, the learning process arises more from discussions and solving problems of students who do not understand the subject matter excellently. Its application has benefits for both teachers and students. Another benefit is being able to answer PAI learning problems. The results of this study have implications for the importance of using the flipped classroom learning model or other cutting-edge learning models to activate students in learning and overcome PAI learning problems.